The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/ijcs.12025
|View full text |Cite
|
Sign up to set email alerts
|

Smart shoppers? Using QR codes and ‘green’ smartphone apps to mobilize sustainable consumption in the retail environment

Abstract: Smartphone-based mobile advertising is a promising marketing vehicle, especially in retail and point-of-purchase environments, yet we still do not know enough about what motivates consumers to turn to mobile advertising. This is particularly true of new forms of mobile advertising, like quick response (QR) codes, which rely on pull-based approaches, rather than push-style advertising. The study clarifies this omission by exploring various antecedents that encourage consumer use of mobile advertising. Relying o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 49 publications
1
69
1
5
Order By: Relevance
“…Although companies frequently try to inform consumers about the green nature of their offerings (e.g., eco-labels, explanations on product packaging, web pages), environmental product claims (e.g., organic, fair trade, biodegradable packaging) fall into the category of credence attributes, which consumers find difficult to assess not only before purchase but also after purchase and use (Atkinson, 2013). This problem is further complicated by recurrent instances of greenwashing misleading consumers about the environmental benefits of a product (Delmas and Burbano, 2011).…”
Section: Outcomes Of Green Skepticismmentioning
confidence: 99%
“…Although companies frequently try to inform consumers about the green nature of their offerings (e.g., eco-labels, explanations on product packaging, web pages), environmental product claims (e.g., organic, fair trade, biodegradable packaging) fall into the category of credence attributes, which consumers find difficult to assess not only before purchase but also after purchase and use (Atkinson, 2013). This problem is further complicated by recurrent instances of greenwashing misleading consumers about the environmental benefits of a product (Delmas and Burbano, 2011).…”
Section: Outcomes Of Green Skepticismmentioning
confidence: 99%
“…However, to the best of our knowledge, there are only a few studies that are tangentially related to this important research question. [9][10][11][12] This study therefore aims to fill this gap by exploring the factors that affect the use of QR codes.…”
Section: Introductionmentioning
confidence: 99%
“…They found that manufacturers who offered organic fibres in their clothing lines were demanding and receiving a premium price. Atkinson's () exploration of eco‐labelling strategies suggested that QR codes and green smartphone apps were effective in eliciting consumption of goods sold in retail stores. In a study exploring the willingness of consumers to pay for eco‐labelled company offerings, demographics were identified as distinguishing factors (Moon et al ., ).…”
Section: Literature Reviewmentioning
confidence: 97%
“…There are mixed findings about this subject in the literature. For example, green smartphone apps were effective in eliciting consumption of goods sold in retail stores eco‐labelling (Atkinson, ), and eco‐labelling may lead to higher market shares (Teisl et al ., ). However, Sedjo and Swallow () found that having eco‐labels did not guarantee businesses to receive price premiums.…”
Section: Introductionmentioning
confidence: 97%